2019
DOI: 10.1155/2019/8638174
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Online Textual Pediatrician-Parent Communication Instrument Based on the SEGUE Framework

Abstract: The prevalence and feature of online textual pediatrician-parent communication (OPPC) have been recognized, but evidence on OPPC assessment remains insufficient. This study aimed to develop and validate an OPPC instrument to provide measurement and quality characteristics for quality assessment and management. 490 OPPC exchanges of 61 tertiary hospitals from 9 Chinese provinces were obtained from the Spring Rain Doctor website. The SEGUE framework, OPPC feature, and a pilot study were considered to establish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…The data of the provider–patient exchanges in this study is reported on the website in public while the content is anonymous for health information sharing. 53 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data of the provider–patient exchanges in this study is reported on the website in public while the content is anonymous for health information sharing. 53 …”
Section: Methodsmentioning
confidence: 99%
“…The data of the provider-patient exchanges in this study is reported on the website in public while the content is anonymous for health information sharing. 53 In China, pharmaceutical services are mainly provided by clinicians. Although services provided by pharmacists have been increasing recently, pharmacist-patient encounter samples online are still limited.…”
Section: Data Collection For Codingmentioning
confidence: 99%
“…The SEGUE framework consists of two sections (doctor–patient communication content and communication skills) and five dimensions (preparation, information collection, information giving, understanding the patient and ending) (Makoul, 2001), and this scale has been used to evaluate communication skills in medical students (Sattler et al., 2017), nursing students (Son & Hee Kim, 2019) and doctors (Bai et al., 2019). The SEGUE framework has a Cronbach's α coefficient, CVI, test–retest reliability and KMO all exceeding 0.8 (Makoul, 2001; Xiong et al., 2019). In this study, 47 emergency department nurses with more than 1 year of professional experience were invited to complete the SEGUE framework and NCAAPS questionnaires, and 32 nurses (68.1%) agreed to participate.…”
Section: The Studymentioning
confidence: 99%
“…In China, few instruments are available for evaluating communication skills, including the Communication Skills Attitude Scale, the SEGUE Framework, and multisource feedback (Zhao et al, 2013 ; Zhang et al, 2018 ; Xiong et al, 2019 ). To the best of our knowledge, however, those tools are widely used among specific professional groups, such as medical students, trainee doctors, nursing probationers, physicians, and nurses (Mendi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%